A Power-Efficient 50 MHz-BW 76.8 dB Signal-to-Noise-and-Distortion Ratio Continuous-Time 2-2 MASH Delta-Sigma Analog-to-Digital Converter with Digital Calibration - Zhiyu Li; Xueqian Shang; Haigang Feng; Xinpeng Xing (Journal of Low Power Electronics and Applications)
Continuous-time Sigma-Delta (CTSD) Analog-to-Digital Converter (ADC) is widely used in wireless receivers due to its built-in anti-aliasing and resistive input. In order to achieve a wide bandwidth while ensuring low power consumption, this paper proposes a CT 2-2 Multi-stAge Noise-sHaping (MASH) ADC for wireless communication. In order to reduce power consumption, the loop filter adopts a feedforward structure, and the operational amplifier uses complementary differential input pairs and feedforward compensation. The pseudo-random sequence injection and Least Mean Squares (LMS) algorithm are adopted to calibrate the digital noise cancelation filter to match the analog transfer function. The simulation results obtained in 40 nm CMOS show that the presented 2-2 CT MASH ADC achieves a 76.8 dB signal-to-noise-and-distortion ratio (SNDR) at a 50MHz bandwidth (BW) with a 1.6 GHz sampling rate and consumes 29.7 mW power under 1.2/0.9 V supply, corresponding to an excellent figure of merit (FoM) of 169.1 dB.